An amplifier for fourth order systems - Aggarwal, G. K. (Defence Science Journal, 2014)
This work presents a circuit for simulating fourth order linear systems using a single operational amplifier. Every one of the three forms discussed is illustrated by one arbitrary simple choice of circuit elements. Simulation is possible for only limited range of values of the systems parameters. The circuit can be extended, by adding more laterally inverted L sections, to simulate higher order linear systems.